The Music of Africa : an introduction - Warren, Fred, 1921-; Warren, Lee.; Naylor, Penelope (Englewood Cliffs, N.J., Prentice-Hall, 1970)
An introduction to African music discussing melody, rhythm and form, musical instruments, and music in traditional and contemporary African life. Includes a bibliography and discography.
Includes bibliography and discography and index.
Keywords: Music -- Africa -- History and criticism